LEUKOSIT DAN LIMFOSIT DALAM TUBERKULOSIS: PRESPEKTIF HEMATOLOGI BERDASARKAN SKALA IUATLD - Kurnia Kusumawati; Sistiyono (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Leukocytes and lymphocytes play a role in the immune response to tuberculosis (TB), but their specific relationship with TB severity remains unclear. This study aims to analyze the association between leukocyte and lymphocyte counts with the IUATLD scale as an indicator of TB severity stratification. This study employed statistical analysis using SPSS version 26. Spearman’s correlation test was used to assess the relationship between leukocyte and lymphocyte counts with the IUATLD scale, while ordinal logistic regression was applied to evaluate the effect of each variable on TB severity stratification. The analysis showed that leukocyte count had a significant but weak correlation with the IUATLD scale (ρ = 0.263, p = 0.002). Conversely, lymphocyte count did not significantly correlate (ρ = 0.092, p = 0.285). Ordinal logistic regression confirmed that leukocyte count had a significant effect on the IUATLD scale (p = 0.018, Estimate = 0.000), whereas lymphocyte count had no statistically significant impact (p = 0.906, Estimate = -1.964E-5). Leukocytes can be used as an additional hematological indicator in TB severity stratification, although their effect is relatively small. In contrast, lymphocytes do not significantly correlate with TB severity, likely due to immune suppression mechanisms induced by Mycobacterium tuberculosis. This study underscores the need for further exploration of other hematological biomarkers to enhance the accuracy of TB severity stratification.